Mechanism of interfacial microstructure evolution of G115 steel in simulated heat affected zone - JIANG Jundong; MA Qingshuang; CHEN Leli; LUO Rui; LI Huijun; GAO Qiuzhi (Cailiao gongcheng)
The microstructure evolution of the interface in the simulated heat affected zone （HAZ） of G115 steel was characterized by electron backscatter diffraction （EBSD） and high resolution transmission electron microscopy （HRTEM）. The results show that the size of precipitated M23C6 in the fine grain zone is smaller than that in the coarse grain and the critical zone， which is only about 100 nm， and the precipitation strengthening effect is obvious. With the increase in peak temperature， the number of small angle grain boundary increases， hence the grain boundary strengthening effect increases. The highest geometrical dislocation density is 3.19×1014 m-2 in the coarse-grained zone. The recovery of the critical dislocation， the pinning of the fine MX precipitates and the appearance of the subgrains make the G115 steel maintain the durable strength for a long time at high-temperature. For the microstructure of the fine grain zone， the increase of welding heat input promotes the transformation of martensitic lath substructure into martensite block substructure， the dislocations are annihilated， the formation of subgrain is inhibited， and the yield strength decreases from 1115 MPa to 947 MPa. When the welding heat input is 14.4 kJ/cm， the microstructure of the fine grain welding heat affected zone has both good strength and toughness.